From Africa to Asia: the shared path of Ethiopia and Cambodia - Riccardo, Corrado; Audrey, Liwan; Tihitena, Melesse (2021)
Geographically, Ethiopia and Cambodia are very far away from each other, but they have more in common than you might imagine. Both countries share a dramatic recent history of violence and difficulties. Nevertheless, they have been capable to rise from the ashes of their past to become two of the fastest-growing economies in the world. But the numbers could be misleading not showing the extremely fragile foundations on which this growth is based. Both countries, in fact, are dangerously lacking appropriate attention on education, committing the same mistake in aiming too high, too fast, without preparing strong underpinnings for sustainable development. Education is a necessary element needed to support the growth of a country, and in this paper, we are going to analyze where Cambodia and Ethiopia stand, focusing on their education sector and highlighting how it is not only their recent pasts and their exceptional economic growth that associate them